Communicating the family firm brand: Antecedents and performance effects. Issue 1 (February 2020) - Beck, Susanne; Prügl, Reinhard; Walter, Katharina
Abstract: Building a family business brand allows family firms to leverage a valuable idiosyncratic resource: their family nature (we are a family business). But, this is only possible if the owning family decides to reveal a family firm image (we want others to know that we are a family business). Family firms largely vary in that regard: While some family firms do strongly emphasize a family firm image, others do so at a lower level or not at all. Accordingly, this study applies mixed methods exploring and testing antecedents of the degree of revealing the family nature of the business in the context of German Mittelstand firms. In study 1, we develop hypotheses for the antecedents of that important managerial decision based on the family business literature as well as interviews with family firm executives. In study 2, we collect data (N = 196) from family firm CEOs to test our hypotheses. Results show that out of eleven antecedents, seven are significantly related to the degree of communicating a family firm image. For example, the tradition orientation of the enterprising family or the number of major business partners being family firms is positively linked to the degree of revealing the family nature, while innovation intensity of the industry or the degree of internationalization of the family firm show a negative relationship with communicating a stronger family firm image. A supplementary exploration of the link between gradual revelation of the family nature and performance on brand and firm level further serves as an inspiration for future research.